Using FEM-AI Technique to Predict the Behavior of Strip Footing Rested on Undrained Clay Layer Improved with Replacement and Geo-Grid - Ahmed M. Ebid; Kennedy C. Onyelowe; Mohamed Salah; Edward I. Adah (Salehan Institute of Higher Education, 2023)
The objective of this research is to predict how strip footings behave when rested on an undrained clay layer enhanced using a top replacement layer with and without a geo-grid. The study was conducted in several stages, including collecting load-settlement curves from